2015
DOI: 10.1177/0004867415610437
|View full text |Cite
|
Sign up to set email alerts
|

People living with psychosocial disability: Rehabilitation and recovery-informed service provision within the second Australian national survey of psychosis

Abstract: Objective: People with psychosocial disability are an important, although often neglected, subgroup of those living with severe and persistent mental illness. Rehabilitation, provided through clinical and non-government organisations in Australia, may contribute to their personal recovery goals. We hypothesised that people with psychoses with the greatest disability and complex needs would receive services from both sectors, reflecting treatment and rehabilitation needs.Method: Participants in the 2010 Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…For example, in Australia in 2010, only 4.7% of people experiencing psychosis and connected to mental health services reported that they participated in peer-led support groups [4]. They could also be offered to people experiencing psychosis who have difficulty socialising [1], or to those who do not have paid employment and are therefore missing out on the contribution that work can make to self-identity and self-esteem in recovery [5,32].…”
Section: Discussion Principal Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in Australia in 2010, only 4.7% of people experiencing psychosis and connected to mental health services reported that they participated in peer-led support groups [4]. They could also be offered to people experiencing psychosis who have difficulty socialising [1], or to those who do not have paid employment and are therefore missing out on the contribution that work can make to self-identity and self-esteem in recovery [5,32].…”
Section: Discussion Principal Findingsmentioning
confidence: 99%
“…This qualitative study was conducted in two Australian clinical community mental health services that provide psychiatric treatment and recovery-oriented services and four non-clinical community mental health services that provide psychosocial rehabilitation and recovery support [4]. Eligible consumer participants were over 18 years of age; with a diagnosis of a psychotic disorder; and had either completed use of the SMART website with a mental health worker employed by the SMART research program, or used the website for at least three months with their usual mental health worker.…”
Section: Recruitment and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial disability often excludes individuals living with this disability from participating in the community through education, employment, recreation, relationships, and adequate housing (Harvey et al, ). Distinct from other forms of psychiatric care, rehabilitation focuses on helping such individuals achieve life goals that are impacted by symptoms and dysfunctions (Killackey, Harvey, Amering, & Herrman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, approximately 16 million Chinese citizens are affected by SMI (Tse, Ran, Huang, & Zhu, ). In Australia, 44% of those with SMI live with the most severe disability and accompanying complex multiagency support needs (Harvey et al, ). There is substantial evidence of the extent of suffering and human rights violations this vulnerable group face across the region (Chatterjee & Hashim, ).…”
Section: Introductionmentioning
confidence: 99%